PENGARUH KONSELING APOTEKER TERHADAP KEPATUHAN PENGGUNAAN OBAT ANTIBIOTIKA: REVIEW - Ulyati Ulfah (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2020)
Antibiotics are drugs used in the therapy of infectious diseases. Non-adherence to antibiotic use can lead to antibiotic resistance. Non-compliance with antibiotic use is generally caused by a patient's lack of understanding of how and the rules for using antibiotics. Providing counseling by pharmacists in providing information, education and motivation related to the use of antibiotics will greatly affect the level of patient compliance so that the therapeutic goals of antibiotic use will be achieved. Based on the results of reviews from several related journals, it was concluded that there was an effect of pharmacist counseling on patient compliance in using antibiotic drugs.